Kemampuan Bakteri Kitinolitik Dalam Menghambat Pertumbuhan Fusarium oxysporum - Rahmiati Rahmiati; Nikmah Ridha Batubara (Journal of Natural Sciences, 2022)
Chitinolytic bacteria have the ability to produce chitinase enzymes, so they have a role in degrading chitin into chitin derivative compounds. The constituent components of chitin are used by various microorganisms capable of producing chitinase enzymes. One such microorganism is bacteria. Chitinolytic bacteria are known to be able to control the growth of pathogenic fungi in plants. Fungal cell walls are composed of various complex compounds including chitin, glucans, mannans and proteins. Based on the composition of these constituents, the enzymes that can hydrolyze the fungal cell wall also vary, namely chitinase, glucanase, protease and mananase. The synergy of these hydrolase enzymes can have a good pathogenic effect in lysing the cell walls of pathogenic fungi. This study aims to determine the potential of chitinolytic bacteria as biological control agents for plant pathogenic fungi. The research was conducted at the Microbiology Laboratory, University of North Sumatra. The research method used is descriptive qualitative. The chitinolytic bacteria used were derived from shrimp shell waste. There were 10 isolates of chitinolytic bacteria tested, namely NR02, NR03, NR04, NR05, NR06, NR07, NR08, NR09, NR10, NR11 and PU01. The results showed that isolates of chitinolytic bacteria from shrimp waste were able to inhibit the fungus Fusarium oxysporum.